A List of 267 French Texts in Tours: A Hub for Reading in the Vernacular (Studi di storia medioevale e di diplomatica - Nuova Serie, 2020)
This article analyses the late fifteenth-century booklist on folios 78r to 82v of Manuscript français 2912 of the Bibliothèque nationale de France in Paris, listing over 267 books in French. A close study of the material aspects of the document itself and of the texts listed in the inventory has allowed for a new dating of the booklist, to shortly after 1494, and for a fairly reliable hypothesis concerning the owner of the books: a bookseller specialising in second-hand books in French. The geographical indication in the booklist, «In Tours in front of the hôtel [town house] of monseigneur de Dunois», can be located in the town on the basis of historical maps: in the Grand Rue (now the rue Colbert) against the southern wall of the church of Saint-Julien or next to its southern and main entrance. Comparison with other book producers and booksellers in Paris and in Flanders shows that this is a typical location. The names and locations of booksellers and artisans active in the production of books in Tours as contained in the notarial archives of the town have unfortunately not permitted an identification of the bookseller, although the printer Simon Pourcelet had his printing workshop and bookshop nearby. Documented lending activities of booksellers in Flanders and the open character of other late medieval libraries and book collections show that this remarkably rich collection of literary, historical, pragmatic, and religious books in French was most likely an open access hub for reading in the vernacular in the bustling heart of late medieval Tours.
Keywords: Booklist; Inventory; Library; Bookseller; Books in French; Tours (France)